Sapwood of carob tree (Ceratonia siliqua L.) as a potential source of bioactive compounds - Custódio, Luísa (2015)
Methanol (ME) and hot water extracts (WE) of carob tree sapwood (Ceratonia siliqua L.) exhibited high antioxidant activity and were rich in phenolic compounds, with the main compounds identified by HPLC/DAD as gentisic acid and (-)-epicatechin. The ME displayed a high in vitro antitumor activity against human tumoural cell lines and reduced intracellular ROS production by HeLa cells after treatment with H2O2. (-)-Epicatechin was shown to contribute to the cytotoxic activity of the ME. This is the first report on the biological activity of carob tree sapwood.